Pertangungjawaban Pidana atas Penyalahgunaan Profesi Wartawan dalam Tindak Pidana Pemerasan - Noviani, Ni Kadek Fitri; Wulandari, Ni Gusti Agung Ayu Mas Tri; Darma, I Made Wirya; Sukadana, Dewa Ayu Putri (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Freedom of the press in Indonesia is constitutionally guaranteed under Article 28F of the 1945 Constitution as a vital pillar of democracy and freedom of expression. However, this freedom is often misused by individuals posing as journalists to commit extortion, thereby undermining the integrity of the press. This study aims to analyze the form of criminal liability imposed on individuals who abuse the journalist profession to conduct extortion accompanied by threats, as regulated in Article 368 of the Indonesian Criminal Code. Using a normative legal research method with a literature-based approach, this study examines legal doctrines, scholarly works, and relevant legislation, including the Press Law and the Criminal Code. The findings indicate that the principle of lex specialis derogat legi generali cannot be applied to such cases because extortion is a general crime, not a press dispute. Therefore, criminal liability falls entirely under the jurisdiction of general criminal law, not the Press Law. The study concludes that the misuse of journalistic attributes as tools for extortion eliminates press privilege and must be prosecuted as an ordinary criminal offense to safeguard press integrity and uphold legal certainty.